Sistema para a medição dos movimentos de um navio amarrado no Posto 'A' do Porto de Leixões baseado em visão estereoscópica [System for Measuring the Motions of a Moored Ship at the Berth 'A' of the Leixões Oil Terminal Based on Stereoscopic Vision] - Paulo Lima Malheiros (2010)
The behavior of moored ships is an important factor in the security and working conditions of the Oil Terminal in the Port of Leixões. Reducing the amplitude of the moored ship motions is crucial to increase the on and off-loading operations efficiency as well as to reduce security and environmental risks. This paper presents a stereoscopic vision system developed to measure the motion of rigid bodies in real-time. The data acquired with this system is essential to predict and prevent dangerous situations at Berth "A" of the Port of Leixões. Prior to installation on site the system was tested in laboratory in physical model (scale 1/100). To ensure the robustness and reliability of the obtained measurements a linear digital filter was implemented. The results obtained with the developed system were compared with a commercial motion capture system built for "in house" applications.